Obstacles to achieving quality field application performance from the point of view of fourth-stage female students at the College of Physical Education and Sports Sciences, University of Baghdad - Khader , Yasir; Fadhel, Mauth; Hamdan, Abdullah (Journal of Physical Education, 2024)
The aim of the research was to prepare a scale of obstacles to achieving quality performance, field application from the point of view of fourth-stage female students, to identifyOn the difficulties and obstacles to achieving quality performance through field application from the students’ point of view for the topic (school administrative procedures, learners, cognitive achievement, school tools).The researchers used the descriptive approach in the research procedures as it is an appropriate approach to achieve the research objectives.,The following questions were asked:There are obstacles and difficulties faced by female students during the process of choosing schools, dealing with school administrations, and the difficulties faced by female students during field application. Therefore, the importance of this study came in knowing the obstacles facing female students.The scale of obstacles to achieving quality performance consisted of 24 paragraphs, as it included four axes, each axis had 6 paragraphs. The first axis was school procedures, the second axis was learners, the third axis was students’ cognitive achievement, and the fourth axis was school tools. The number of fourth-stage female students reached 128 female students who graduated for the academic year 2022-2023. A proportional random research sample was chosen at a rate of 78.12% From 100 students.The researchers concluded that the scale of obstacles to achieving quality performance field application from the point of view of fourth-stage female students in the College of Physical Education and Sports Sciences, University of Baghdad, the quality of field application depends entirely on school variables (school tools and procedures and knowledge of students and learners) and the researchers recommend that there be a scientific study regarding the quality of schools before field application, developing educational methods and approaches in colleges for implementers, having the sports lesson at the beginning of the school schedule, holding workshops with school principals to develop the field application process.